(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
With the switch from traditional data datacenter towards the cloud, demand for cloud storage has increased rapidly. The major issue about cloud storage is providing security for remotely stored data and for deploying applications, which led to abundant consideration of storage security issues. In this paper we report the issues faced while using a cloud environment. Further, we address a scheme known as Provable Data Possession (PDP) that verifies the integrity of the data stored without having to download it from the cloud when expected. This scheme provides dynamic storage and dynamic operation. The theoretical analysis for this scheme showed its support for multi-user operations. This scheme has overcome the flaw of single-block storage.